The Arms Race in an Era of Negotiations - Carlton, David. author. aut Link
XXVII, 265 p.
Keywords: The countries of NATO and the Warsaw Pact have begun to negotiate for nuclear and conventional arms reductions. The world is no longer bipolar, as the arsenals of China, France and Britain become more significant. This book looks at strategic realities and current global and European problems.